Free functional muscle transfer for upper limb paralysis - a systematic review - Reed, AJ; Claireaux, HA; Wormald, JC; Thurley, N; Shirley, R; Chan, JK (Elsevier, 2021)
Background: Functional restoration of upper limb paralysis represents a major reconstructive challenge. Free functional muscle transfer (FFMT) enables reanimation in patients with a lack of local donor tissues or delayed presentation. This systematic review summarises the evidence for FFMT in the reconstruction of upper limb paralysis.